1985
DOI: 10.1056/nejm198503143121102
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Results of a Randomized Clinical Trial Comparing Radical Mastectomy and Total Mastectomy with or without Radiation

Abstract: In 1971 we began a randomized trial to compare alternative local and regional treatments of breast cancer, all of which employ breast removal. Life-table estimates were obtained for 1665 women enrolled in the study for a mean of 126 months. There were no significant differences among three groups of patients with clinically negative axillary nodes, with respect to disease-free survival, distant-disease--free survival, or overall survival (about 57 per cent) at 10 years. The patients were treated by radical mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
313
0
9

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,258 publications
(330 citation statements)
references
References 20 publications
8
313
0
9
Order By: Relevance
“…However, we believe it was adequate, because >75% of the regional recurrences observed in the NSABP B-04 trial occurred within the first 24 months of surgery. 38 In contrast to the B-04 trial, a high percentage of patients in our study received systemic therapy, which greatly contributes to the low locoregional recurrence rates reported in patients with early stage breast cancer. 39,40 It is possible that longer surveillance may reveal an increase in axillary recurrences that initially were tempered by the receipt of systemic therapy.…”
Section: (7)mentioning
confidence: 86%
“…However, we believe it was adequate, because >75% of the regional recurrences observed in the NSABP B-04 trial occurred within the first 24 months of surgery. 38 In contrast to the B-04 trial, a high percentage of patients in our study received systemic therapy, which greatly contributes to the low locoregional recurrence rates reported in patients with early stage breast cancer. 39,40 It is possible that longer surveillance may reveal an increase in axillary recurrences that initially were tempered by the receipt of systemic therapy.…”
Section: (7)mentioning
confidence: 86%
“…Fisher et al were the first to support the hypothesis that axillary dissection has prognostic significance [23]. This led to the use of various options in the management of axilla, including axillary dissection, axillary clearance, axillary dissection with regional lymph node radiation, regional radiation alone, axillary sampling, endoscopic axillary clearance, sentinel lymph node biopsy, and observation [23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, they also started questioning the extent of surgery for early stage breast cancer. In the 80s, two large studies namely the NSABP-B04 and the King's-Cambridge trials published their 10-year follow-up results after comparing AD plus radiotherapy (RT) with no treatment to the axilla in clinically node-negative patients [5][6]. In both studies, treating the axilla did decrease the recurrence rate significantly (1.4% for AD, 3.1% for RT, and 14% for no treatment), but did not improve the survival rate in early stage breast cancer patients.…”
Section: Reviewmentioning
confidence: 99%
“…The NSABP-B04 trial also reported a 40% metastatic rate on final pathology in clinically nodenegative patients but if the axilla did not receive any local treatment only a 15% axillary recurrence was identified [5]. After 1990s with breast cancer screening programs becoming more widely used, the rate of axillary positivity decreased to 22% [7].…”
Section: Reviewmentioning
confidence: 99%